Relationships between Serotonin Transporter Binding in the Raphe Nuclei, Basal Ganglia, and Hippocampus with Clinical Symptoms in Cervical Dystonia: A [11C]DASB Positron Emission Tomography Study - Smit, Marenka; Vállez García, David; de Jong, Bauke M.; Zoons, Evelien; Booij, Jan; Dierckx, Rudi A.; Willemsen, Antoon T.; de Vries, Erik F.; Bartels, Anna L.; Tijssen, Marina A. (Frontiers in Neurology, 2018)
Purpose: Alterations of the central serotonergic system have been implicated in the pathophysiology of dystonia. In this molecular imaging study, we assessed whether altered presynaptic serotonin transporter (SERT) binding contributes to the pathophysiology of cervical dystonia, concerning both motor and non-motor symptoms (NMS). Methods: We assessed the non-displaceable binding potential (BPND) using the selective SERT tracer [11C]DASB and positron emission tomography (PET) in 14 CD patients and 12 age- and gender-matched controls. Severity of motor symptoms was scored using the Toronto Western Spasmodic Torticollis Rating Scale and Clinical Global Impression jerks/tremor scale. NMS for depressive symptoms, anxiety, fatigue and sleep disturbances were assessed with quantitative rating scales. The relationship between SERT binding and clinical patient characteristics was analyzed with the Spearman’s rho test and multiple regression. Results: When comparing the CD patients with controls, no significant differences in BPND were found. Higher BPND in the dorsal raphe nucleus was statistically significantly correlated (p<0.001) with motor symptom severity (rs=0.65), pain (rs=0.73) and sleep disturbances (rs=0.73), with motor symptom severity being the most important predictor of SERT binding. Furthermore, fatigue was negatively associated with the BPND in the medial raphe nucleus (rs=-0.61, p=0.045), and sleep disorders were positively associated with the BPND in the caudate nucleus (rs=0.58, p=0.03) and the hippocampus (rs=0.56, p=0.02). Conclusions: Motor symptoms, as well as pain, sleep disturbances and fatigue in CD showed a significant relationship with SERT binding in the raphe nuclei. Also, fatigue showed a significant relationship with the medial raphe nucleus and sleep disorders with the caudate nucleus and hippocampus. These findings suggest that an altered serotonergic signaling in different brain areas in CD is related to different motor as well as non-motor symptoms, which will further stimulate research on the role of serotonin in the pathogenesis of dystonia.